Establishing a set of qualities for clinical teaching faculty in undergraduate medical internship - Jiangman Song; Ge Wei; Huaqin Cheng; Yonghong Yan; Shuya Yang (BMC Medical Education)
Abstract Background In the medical education system of China, the contents of the undergraduate medical internship included practicing theoretical knowledge, clinical skills, communication ability, and human care in the teaching hospital. Multiple teaching objectives are encompassed in the teaching of this phase, which is significantly influenced by the environment. The abilities of this workplace-based teaching are difficult to observe and assess. The concepts of competency and entrustable professional activities (EPAs) are applied largely in education. This study aims to establish a set of qualities by merging competency and EPAs for clinical teaching faculty during the undergraduate medical internship. Methods Literature research, theoretical analysis, and focus group interviews on teaching abilities in the internship were conducted by our study group, followed by discussion among 9 experts in education/pedagogy and medical education from 6 institutions. The framework of qualities was drafted and formulated with item titles, definitions, and explanations. Then we sent the framework to another 50 clinical teachers and teaching administrators from two medical universities and three teaching hospitals in different regions. The content validation was completed with two rounds of modified Delphi procedure. The entropy weight method was utilized to calculate the weight of each indicator. Results The response rate was 100% during the two Delphi rounds. Each item and the content description was revised and consensus was reached. The qualities of clinical teaching faculty in undergraduate medical internship comprised 11 items, which were categorized into three domains: education and teaching literacy, clinical skills instruction, and professional knowledge and application. Conclusion This study applied a scientific, comprehensive, and systematic Delphi procedure and established qualities for clinical teaching faculty during the undergraduate medical internship with the concept of merging competency and EPAs. Our report on the qualities of clinical teachers may guide the assessment and development of faculty members.